FBXW7 expression affects the response to chemoradiotherapy and overall survival among patients with oral squamous cell carcinoma: A single-center retrospective study. Issue 10 (October 2017) - Arita, Hidetaka; Nagata, Masashi; Yoshida, Ryoji; Matsuoka, Yuichiro; Hirosue, Akiyuki; Kawahara, Kenta; Sakata, Junki; Nakashima, Hikaru; Kojima, Taku; Toya, Ryo; Murakami, Ryuji; Hiraki, Akimitsu; et al.
FBXW7 (F-box and WD repeat domain containing-7) is a tumor suppressor protein that regulates the degradation of various oncoproteins in several malignancies. However, limited information is available regarding FBXW7 expression in oral squamous cell carcinoma. Therefore, this study aimed to determine the clinical significance of FBXW7 expression in oral squamous cell carcinoma. The FBXW7 expression patterns in oral squamous cell carcinoma and adjacent normal tissues from 15 patients who underwent radical resection were evaluated using quantitative real-time polymerase chain reaction and immunohistochemical staining. In addition, immunohistochemistry was performed using paraffin-embedded sections from biopsy specimens obtained from 110 patients with oral squamous cell carcinoma who underwent surgery after 5 fluorouracil-based chemoradiotherapy. The associations of FBXW7 expression with various clinicopathological features and prognosis were evaluated in these patients. As a results, in the 15 matched samples, the FBXW7 expression was significantly decreased in the oral squamous cell carcinoma tissues compared to that in the adjacent normal tissues. In the clinicopathological analysis, compared to high protein expression, low FBXW7 expression was found to significantly associate with a poor histological response to preoperative chemoradiotherapy. Kaplan–Meier curve analysis revealed that low FBXW7 expression was significantly associated with a poor prognosis, and FBXW7 expression was found to be an independent predictor of overall survival in the multivariate analysis. Our results suggest that FBXW7 may function as a tumor suppressor protein in oral squamous cell carcinoma. In addition, FBXW7 could be a potential biomarker for predicting not only the clinical response to chemoradiotherapy but also overall survival in patients with oral squamous cell carcinoma.